SỬ DỤNG COPOLIME KHỐI PLURONIC TRONG QUÁ TRÌNH TỔNG HỢP Me-SBA-16 (Me: Al, Fe) VÀ ĐÁNH GIÁ KHẢ NĂNG ỨNG DỤNG TRONG VIỆC XỬ LÝ CHẤT THẢI HỮU CƠ CÔNG NGHIỆP - Núi, Phạm Xuân; Lý, Lê Đình (Vietnam Journal of Chemistry, 2012)
Al-SBA-16 and Fe-SBA-16 were successfully synthesized by direct hydrothermal method. The obtained materials were characterized by diferent techniques such as powder X-raydiffractions (XRD), transmission electron microscopy (TEM), nitrogen adsorption/desorption measurement, diffuse reflectance UV-Visible spectroscopy (UV-Vis) the obtained results showed that the prepared samples are highly ordered cubic mesostructure with a large specific surface area and a uniform mesopore size distribution. The catalytic activity of obtained samples was tested in the oxidation of phenol and red-phenol. The analysis of oxidation products using HPLC. The catalytic result showed that Al-SBA-16 and Fe-SBA-16 exhibit a high catalytic activity for total oxidation of phenol and phenol red.